Cell coupling in mouse pancreatic beta-cells measured in intact islets of Langerhans. - Zhang, Q; Galvanovskis, J; Abdulkader, F; Partridge, C; Göpel, S; Eliasson, L; Rorsman, P (2008)
The perforated whole-cell configuration of the patch-clamp technique was applied to functionally identified beta-cells in intact mouse pancreatic islets to study the extent of cell coupling between adjacent beta-cells. Using a combination of current- and voltage-clamp recordings, the total gap junctional conductance between beta-cells in an islet was estimated to be 1.22 nS. The analysis of the current waveforms in a voltage-clamped cell (due to the firing of an action potential in a neighbouring cell) suggested that the gap junctional conductance between a pair of beta-cells was 0.17 nS. Subthreshold voltage-clamp depolarization (to -55 mV) gave rise to a slow capacitive current indicative of coupling between beta-cells, but not in non-beta-cells, with a time constant of 13.5 ms and a total charge movement of 0.2 pC. Our data suggest that a superficial beta-cell in an islet is in electrical contact with six to seven other beta-cells. No evidence for dye coupling was obtained when cells were dialysed with Lucifer yellow even when electrical coupling was apparent. The correction of the measured resting conductance for the contribution of the gap junctional conductance indicated that the whole-cell KATP channel conductance (GK,ATP) falls from approximately 2.5 nS in the absence of glucose to 0.1 nS at 15 mM glucose with an estimated IC50 of approximately 4mM. Theoretical considerations indicate that the coupling between beta-cells within the islet is sufficient to allow propagation of [Ca2+]i waves to spread with a speed of approximately 80 microms-1, similar to that observed experimentally in confocal [Ca2+]i imaging.